عمل المرأة في العصر المملوكي: دراسة في تاريخ الإجتماع - Muhammad, Abdullahi Abubakar (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2025)
AbstractThis research challenges the stereotypes perpetuated by Orientalists and Western scholars that portray women in Islamic societies as oppressed and excluded from social and economic life. Through an analysis of historical records from the Mamluk era (1250–1517 CE), utilizing Women’s History Collections of the Mamluk Era as a source of social history and adopting the emancipatory approach, this study reveals the significant roles women played in education, healthcare, trade, and charitable work. The study examines the legal and social frameworks governing women’s work and property rights, highlighting the agency and autonomy women exercised in their daily lives. By contextualizing this historical evidence within the broader discourse of social history and Islamic studies, the research refutes prevailing stereotypes and offers a more nuanced and comprehensive understanding of women’s experiences in Islamic societies. Thus, this research contributes to a more informed and inclusive discussion on social history within the context of Islamic society.